Peningkatan Pengetahuan Tanggap Bencana Kebakaran Melalui VBE - Tendean, Angelia Friska; Basrudin, Basrudin; Lestari, Nina Dwi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Knowledge of fire disaster response is very necessary to avoid the risk of fire hazards that can occur such as loss of property, injury and even loss of life. The results of the preliminary assessment found that most of the education staff and cleaning service had not received information related to fire disaster response including independent evacuation, around 37 participants (59.5%) were less responsive to fire. Therefore, the community service team conducted fire disaster response counseling through Video Based Education (VBE) to increase the knowledge of educational staff and cleaning service at the Siti Walidah building, University of Muhammadiyah Yogyakarta (UMY). This method of implementing community service activities is carried out by providing education through video media which contains fire prevention in the building and self-evacuation. The results of the implementation of community service activities showed an increase in knowledge about fire disasters among education staff and cleaning service from a less level of knowledge 54%, moderate 46% and high 6% to a high level of knowledge 44%, moderate 39% and less 17%. Through the implementation of community service activities with education using VBE, it can improve knowledge of fire disaster response for education staff and cleaning service at the Siti Walidah UMY building.Keywords:, Disaster Response, Education, Fire, Knowledge Video Based Education